The Welleye: A Conceptual Framework for Understanding and Promoting Wellbeing - Dolan, Paul; Laffan, Kate; Kudrna, Laura (Frontiers in Psychology, 2021)
We present the Welleye – a novel and conceptually clear framework that shows how attention links the objective circumstances of people’s lives and selves to how they spend their time and feel day to day. While existing wellbeing frameworks in policy contain many of the factors included in the Welleye, they all lack attention as the “lens” that determines the impact of these factors on how people feel. Policymakers and organizations can use the Welleye to better understand how people are faring and design and evaluate interventions aimed at making people better off.